Differential regulation of amyloid-beta-protein mRNA expression within hippocampal neuronal subpopulations in Alzheimer disease. - Higgins, G A (1988)
We have mapped the neuroanatomical distribution of amyloid-beta-protein mRNA within neuronal subpopulations of the hippocampal formation in the cynomolgus monkey (Macaca fascicularis), normal aged human, and patients with Alzheimer disease. Amyloid-beta-protein mRNA appears to be expressed in all hippocampal neurons, but at different levels of abundance. In the central nervous system of monkey and normal aged human, image analysis shows that neurons of the dentate gyrus and cornu Ammonis fields contain a 2.5-times-greater hybridization signal than is present in neurons of the subiculum and entorhinal cortex. In contrast, in the Alzheimer disease hippocampal formation, the levels of amyloid-beta-protein mRNA in the cornu Ammonis field 3 and parasubiculum are equivalent. These findings suggest that within certain neuronal subpopulations cell type-specific regulation of amyloid-beta-protein gene expression may be altered in Alzheimer disease.